Requirement of DLG1 for cardiovascular development and tissue elongation during cochlear, enteric, and skeletal development: possible role in convergent extension. - Akiko Iizuka-Kogo; Takao Senda; Tetsu Akiyama; Atsushi Shimomura; Ryuji Nomura; Yoshimi Hasegawa; Ken-Ichi Yamamura; Hiroshi Kogo; Nobuhiko Sawai; Toshiyuki Matsuzaki (PLoS ONE, 2015)
The Dlg1 gene encodes a member of the MAGUK protein family involved in the polarization of epithelial cells. Null mutant mice for the Dlg1 gene (Dlg1-/- mice) exhibit respiratory failure and cyanosis, and die soon after birth. However, the cause of this neonatal lethality has not been determined. In the present study, we further examined Dlg1-/- mice and found severe defects in the cardiovascular system, including ventricular septal defect, persistent truncus arteriosus, and double outlet right ventricle, which would cause the neonatal lethality. These cardiovascular phenotypes resemble those of mutant mice lacking planar cell polarity (PCP) genes and support a recent notion that DLG1 is involved in the PCP pathway. We assessed the degree of involvement of DLG1 in the development of other organs, as the cochlea, intestine, and skeleton, in which PCP signaling has been suggested to play a role. In the organ of Corti, tissue elongation was inhibited accompanied by disorganized arrangement of the hair cell rows, while the orientation of the stereocilia bundle was normal. In the sternum, cleft sternum, abnormal calcification pattern of cartilage, and disorganization of chondrocytes were observed. Furthermore, shortening of the intestine, sternum, and long bones of the limbs was observed. These phenotypes of Dlg1-/- mice involving cellular disorganization and insufficient tissue elongation strongly suggest a defect in the convergent extension movements in these mice. Thus, our present results provide a possibility that DLG1 is particularly required for convergent extension among PCP signaling-dependent processes.